Study of wear resistance and nanostructure of tertiary Al2O3/Y2O3/CNT pulsed electrodeposited Ni-based nanocomposite - Mirzamohammadi, S.; Aliov, M.Kh.; Sabur, A.R.; Hassanzadeh-Tabrizi, A. (Фізико-хімічна механіка матеріалів, 2010)
Electrodeposition of tertiary Alumina/Yitria/carbon nanotube (Al2O3/Y2O3/CNT) nanocomposite by using pulsed current has been studied. Coating process has been performed in nickel sulphate bath and nanostructure of the obtained compound layer was examined with high precision figure analysis of SEM nanographs. The effects of process variables, i.e. Y2O3 concentration, treatment time, current density and temperature of electrolyte have been experimentally studied. Statistical methods were used to achieve the minimum wear rate and average size of nanoparticles. Finally the contribution percentage of different effective factors was revealed and confirmation run showed the validity of the obtained results. Also it has been revealed that by changing the size of nanoparticles, wear properties of coatings will change significantly. Atomic force microscopy (AFM) and transmission electron microscope (TEM) analysis have confirmed smooth surface and average size of nanoparticles in the optimal coating. Вивчено електроосадження методом імпульсного струму потрійного композиту на основі вуглецевих нанотрубок, алюмінію та ітрію оксидів. Покриви наносили у нікелесульфатній ванні, а наноструктуру отриманого складного шару досліджували методом комп’ютерного аналізу знімків, одержаних на електронному мікроскопі. Вплив змінних параметрів процесу, зокрема, концентрації Y2O3, часу обробки, густини струму та температури електроліту вивчали експериментально. Для мінімізації впливу відхилень швидкості зношування та середнього розміру наночастинок на аналіз експериментальних даних використовували статистичні методи. Встановлено процентний вклад різних факторів і виконано підтверджувальний розрахунок, який показав достовірність одержаних результатів. Також виявлено, що зміна розміру наночастинок та зносотривкість покривів матиматимуть значною мірою однаковий тренд. Изучено электроосаждение методом импульсного тока тройного композита на основе углеродных нанотрубок, алюминия и иттрия оксидов. Покрытия наносили в никельсульфатной ванне, а наноструктуру полученного сложного слоя исследовали методом компьютерного анализа снимков, полученных на электронном микроскопе. Влияние изменяющихся параметров процесса, в частности, концентрации Y2O3, времени обработки, плотности тока и температуры электролита изучали экспериментально. Для минимизации влияния отклонений скорости изнашивания и среднего размера наночастиц на анализ экспериментальных данных использовали статистические методы. Установлен процентный вклад разных факторов и проведен подтверждающий расчет, который показал достоверность полученных результатов. Также установлено, что изменение размера наночастиц и износостойкость покрытий имеют в значительной степени одинаковый тренд.